Destination Website Quality dan Online Destination Brand Experience: Studi Pada Kota Tua Jakarta dan Kepulauan Seribu - Maulina, Anita; Santoso, Teguh; Arizona, Anisa (Journal of Indonesian Tourism, Hospitality and Recreation, 2024)
ABSTRACTThis research aims to determine and analyze the influence of destination website quality, sensory online destination brand experience, cognitive online destination brand experience, attitude toward the website and intention to visit which are applied to the tourist website of Kota Tua Jakarta and the Thousand Islands. This research uses a quantitative approach using primary data collected from August to October 2023. Questionnaires were distributed to visitors to the Kota Tua Jakarta and Thousand Islands tourist website. 221 questionnaires data can be collected and then processed using Structural Equation Modeling with SmartPLS software. The results of data processing show that not all hypotheses can be accepted. Several suggestions are given for developing further studies and developing website management strategies to achieve increased tourist visits to the Kota Tua Jakarta and the Thousand Islands.ABSTRAKPenelitian ini bertujuan untuk mengetahui dan menganalisis pengaruh variabel destination website quality, sensory online destination brand experience, cognitive online destination brand experience, attitude toward the website, dan intention to visit yang diaplikasikan pada website wisata Kota Tua Jakarta dan Kepulauan Seribu. Penelitian ini menggunakan pendekatan kuantitatif menggunakan data primer berupa kuesioner yang dikumpulkan selama bulan Agustus sampai dengan Oktober 2023. Kuesioner disebarkan kepada pengunjung website wisata Kota Tua Jakarta dan Kepulauan Seribu. Sebanyak 221 data kuesioner dapat dikumpulkan dan kemudian diolah lebih lanjut menggunakan Structural Equation Modelling dengan memanfaatkan software SmartPLS. Hasil olah data menunjukkan bahwa tidak seluruh hipotesis dapat diterima. Beberapa saran diberikan untuk pengembangan studi lebih lanjut serta pengembangan strategi pengelolaan website demi mencapai peningkatan kunjungan wisata ke Kota Tua Jakarta dan Kepulauan Seribu.